Twenty-seven new species of the goblin spider genus Neoxyphinus Birabén, 1953 (Araneae: Oonopidae) from Brazil - Feitosa, Níthomas M.; Moss, Daniella F.; Ruiz, Gustavo R. S.; Bonaldo, Alexandre B. (Zootaxa, 2017)
Twenty-seven new species of the genus Neoxyphinus are described, all from Brazil, raising the total number of species of the genus to 48. The new species with the respective geographic distribution and known sexes are: N. capiranga sp. nov. (♂♀) from Amazonas, Pará, Mato Grosso and Rondônia; N. caprichoso sp. nov. (♂♀) and N. garantido sp. nov. (♂♀) from Amazonas and Pará; N. crasto sp. nov. (♂♀) from Bahia and Sergipe; N. murici sp. nov. (♂♀) from Alagoas and Sergipe; N. meurei sp. nov. (♀) from Bahia and Mato Grosso; N. belterra sp. nov. (♂♀) from Pará and Mato Grosso; N. ornithogoblin sp. nov. (♂♀), N. sax sp. nov. (♂♀), N. coari sp. nov. (♂♀), N. tucuma sp. nov. (♂♀), N. ducke sp. nov. (♂) and N. carigoblin sp. nov. (♀) from Amazonas; N. almerim sp. nov. (♂), N. mutum sp. nov. (♂♀), N. caxiuana sp. nov. (♂♀), N. cachimbo sp. nov. (♂) and N. jacareacanga sp. nov. (♀) from Pará; N. paraty sp. nov. (♂♀) and N. rio sp. nov. (♂♀) from Rio de Janeiro; N. novalima sp. nov. (♂♀) and N. celluliticus sp. nov. (♂) from Minas Gerais; N. paraiba sp. nov. (♂) and N. simsinho sp. nov. (♂♀) from Paraíba; N. cantareira sp. nov. (♂) from São Paulo; N. cavus sp. nov. (♂) from Espírito Santo and N. stigmatus sp. nov. (♂) from Bahia. A key for identification of all 48 known species of Neoxyphinus is provided and possible monophyletic lineages within the genus are discussed.